2001
DOI: 10.1136/jmg.38.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the connexin-26 M34T variant: identification of genotype M34T/M34T segregating with mild-moderate non-syndromic sensorineural hearing loss

Abstract: Mutations in the human gap junction -2 gene (GJB2) that encodes connexin-26 have been shown to cause non-syndromic sensorineural hearing loss (NSSNHL) at the DFNB1 locus on 13q11. Functional and genetic data regarding the disease causing potential of one particular GJB2 sequence variant, 101 T→C (M34T), have proven contradictory. In this study, we found the prevalence of the M34T allele in a cohort of white sib pairs and sporadic cases with NSSNHL from the United Kingdom and Ireland to be 3.179% of chromosomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
81
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 25 publications
9
81
1
1
Order By: Relevance
“…The frequency of the M34T allele in the French control population reported here (1.72%) is consistent with prevalence found in other populations: 25 1.5% in the USA, 8 2.4% in Belgium, 26 1.98% in the UK, 11 1.33% in the Grampian region. 27 In another way, this variant seems to be rare in Asia.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The frequency of the M34T allele in the French control population reported here (1.72%) is consistent with prevalence found in other populations: 25 1.5% in the USA, 8 2.4% in Belgium, 26 1.98% in the UK, 11 1.33% in the Grampian region. 27 In another way, this variant seems to be rare in Asia.…”
Section: Discussionsupporting
confidence: 75%
“…12,11,18,10,23,13,24 However, as Griffith et al 10 we reported here five normal hearing subjects carrying a compound heterozygous mutation in which the M34T substitution is associated in trans with a truncated mutation : the 35delG GJB2 mutation or the (GJB6-D13S1830)del. 20 These results indicate that M34T is not a recessive mutation responsible for hearing loss.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…However, the M34T allele was sometimes found as a compound heterozygote among individuals with hearing loss, 7,30,34,39,46,49 -52 and more rarely, in the homozygous form in individuals with hearing loss. 39,51,53 No changes have been reported in the other allele among the M34T carriers in the control groups. Thus, the evidence appears to support the hypothesis that M34T is a recessive allele, although the lack of compound heterozygotes in the control groups may be due to their smaller sample sizes.…”
Section: M34t Allele and Hearing Lossmentioning
confidence: 93%